Pelatihan Siswa Tanggap Bencana sebagai Upaya Mitigasi Bencana di Ponorogo: Training of Disaster Responsive Students as Disaster Mitigation Efforts in Ponorogo - Sukamto, Filia Icha; Nurhidayat, Saiful; Verawati, Metti (Amalee: Indonesian Journal of Community Research and Engagement, 2021)
Around 40.9 million Indonesians live in landslide prone areas. In the Ponorogo regency of the East Java province, there are 9 sub-districts that have been designated as landslide prone areas with the mild to severe category. One of the villages has experienced landslides in 2017, Banaran village of Pulung district, which 28 villagers became victim and 23 houses buried. Children are virtually one of the most vulnerable groups to being affected by disasters. The vulnerability of children to disasters is triggered by a limited risk understanding which results in a lack of preparedness in facing disasters. Achieving school preparedness is very important considering that Indonesia is a country with a high risk of disasters. It is very important to raise awareness of disasters as early as possible to minimize the impact of disaster risks. The preparedness of the school component is still below expectations, the regulations formed by providing education and simulations to students about disaster response and the impact of disasters are able to reduce disaster risk considering that children are one of the vulnerable groups. We counseled students of SDN Bekiring in Ponorogo to instill their understanding about landslide disaster mitigation. Sekitar 40,9 juta penduduk Indonesia tinggal di daerah rawan longsor. Di Kabupaten Ponorogo Provinsi Jawa Timur, terdapat 9 kecamatan yang telah ditetapkan sebagai daerah rawan longsor dengan kategori ringan sampai berat. Salah satu desa yang pernah mengalami longsor pada tahun 2017 adalah Desa Banaran Kecamatan Pulung yang mengakibatkan 28 warga menjadi korban dan 23 rumah tertimbun. Anak-anak sebenarnya merupakan salah satu kelompok yang paling rentan terkena bencana. Kerentanan anak terhadap bencana dipicu oleh pemahaman risiko yang terbatas yang berakibat pada kurangnya kesiapsiagaan dalam menghadapi bencana. Mewujudkan kesiapsiagaan sekolah menjadi sangat penting mengingat Indonesia merupakan negara dengan risiko bencana yang tinggi. Sangat penting untuk meningkatkan kesadaran bencana sedini mungkin untuk meminimalkan dampak risiko bencana. Kesiapsiagaan komponen sekolah masih dibawah ekspektasi, regulasi yang dibentuk dengan memberikan edukasi dan simulasi kepada siswa tentang tanggap bencana dan dampak bencana mampu mengurangi risiko bencana mengingat anak merupakan salah satu kelompok rentan. Kami mendampingi siswa SDN Bekiring di Ponorogo untuk menanamkan pemahaman tentang mitigasi bencana longsor.